A novel acidic deep eutectic solvent for sustainable and efficient coumarin synthesis - Fatemeh Mohammad; Najmedin Azizi; Zohreh Mirjafari; Javad Mokhtari (Scientific Reports)
Abstract A novel acidic deep eutectic solvent (ADES) has been developed as an efficient and sustainable alternative to traditional solvents and catalysts in organic synthesis. The ADES was synthesized through a simple one-pot procedure involving benzyl chloride, 2-(dimethylamino)ethanol, and p-toluenesulfonic acid, yielding a homogeneous liquid. Structural and compositional characterization was performed using FTIR and NMR spectroscopy. The catalytic performance of the synthesized ADES was evaluated in the Pechmann condensation for the synthesis of coumarins. The reaction proceeded under mild conditions using commercially available starting materials, with reaction times ranging from 5 to 200 min and isolated yields between 72% and 97%. The process is operationally simple and readily scalable, indicating its suitability for industrial implementation. Importantly, the ADES demonstrated excellent recyclability, maintaining catalytic activity over five consecutive cycles without significant loss of efficiency which makes it an environmentally friendly and economically viable option for large-scale synthesis.